Studies in the Hebrew Bible, Qumran, and the Septuagint presented to Eugene Ulrich - Ulrich, Eugene Charles, 1938-; Flint, Peter W.; VanderKam, James C.; Tov, Emanuel. (Supplements to Vetus Testamentum,, 2006)
With contributions by many of his colleagues and former students, this volume pays homage to Eugene Ulrich, Chief Editor of the Cave 4 Biblical Scrolls and a foremost expert on the Biblical Scrolls, the Canon of the Hebrew Bible/Old Testament, and the Septuagint. In line with Professor Ulrich's areas of scholarship and interest, the almost 30 essays are grouped in three main sections: The Hebrew Bible/Old Testament (including the Biblical Scrolls from the Judaean Desert); Qumran and the Non-Biblical Scrolls from the Judaean Desert; and the Septuagint and Other Ancient Versions. The volume includes a tribute to Eugene Ulrich and ends with a cumulative bibliography and several useful indices.